Integrated instrumentation for combined laser-induced breakdown and Raman spectroscopy. Issue 4 (4th July 2019) - Guo, Guangmeng; Liu, Ke; Wang, Jie; Wang, Shuai; Lin, Qingyu; Ding, Yu; Tian, Di; Duan, Yixiang
Abstract: Laser-induced breakdown spectroscopy (LIBS) is capable of providing elemental analysis while Raman spectroscopy is powerful for molecular and structural characteristics of crystalline substances. This work proposes an innovative hybridized instrument to simultaneously obtain molecular and elemental information on an analyte. The instrument was designed in a compact form due to the integration of a modularized structure and a single unified control system, which was ultimately restricted to a size of 420 mm × 520 mm × 650 mm, suitable for field applications. An orthogonal optical system was used to focus the laser beams and obtain the spectra and real-time imaging of the tested area. A pulsed laser (1064 nm, 100 mJ, 1–20 Hz) and a continuous-wave laser (532 nm, 22 mW) were applied for LIBS and Raman measurements, respectively. The multichannel original equipment manufactured spectrometer ensures a wide spectral range (185–850 nm for LIBS and 400–4000 cm −1 for Raman) on the basis of its low weight. A central control circuit board was specially developed by integrating the control command and data transmission to achieve centralized control of the components, thereby providing precise timing control and improving the instrument. The enclosed sample chamber had the function of mapping and shielding the fill gas. The developed client software provided a comprehensive operation interface. Ammonium persulfate and carbonate were used to demonstrate the feasibility of the developed hybrid instrument to obtain the element and molecular structural information of analytes.